Caregiver Burden for Patients Diagnosed with Parkinson’s Disease: A Cross-sectional Study from Southern India - Arun Kurupath; Praveen Arathil; Rahul Bansal (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Parkinson’s Disease (PD) is a progressive neurodegenerative disorder where the individual over time needs more and more assistance from their caregivers to carry on their life and that causes increasing burden on the caregiver. The burden for the caregiver is affecting them physically, mentally and also on a socioeconomic level. Aim: To examine the factors related to caregiver burden in caregivers of Parkinson’s patients. Materials and Methods: This was a cross-sectional study conducted in Parkinson’s clinic of a Tertiary Care Hospital of Kochi, on 100 Parkinsonism patients and their respective caregivers. Patients were assessed using the Unified PD Rating Scale (UPDRS), Hoehn and Yahr Scale (H&Y) and Mini-Mental State Examination (MMSE). Caregivers were assessed using Zerit’s Caregiver Burden inventory (CBI). Semi structured questionnaire was administered for socio-demographic details. Non parametric tests were done to examine the correlation among various variables. Results: Among the patients and caregivers, mean age was 70.65±7.30 and 67.31±8.56, respectively. Among the patient’s majority were males (n=74) while among caregivers, majority were females (n=73). Mean duration of disease was 6.79±2.68 years, mean caregiver burden score was 65.05±21.79, mean UPDRS score was 21.89±8.74 and had significant positive correlation with caregiver burden. Mean MMSE score was 17.19±4.91. The disease duration and UPDRS score had a significant positive correlation with caregiver burden score. MMSE score had significant negative correlation with caregiver burden score. Conclusion: This study concludes that a patient’s Parkinsonism related disability accounts for majority of caregiver burden. An early identification of factors contributing to stress in caregivers will help to avoid its persistency leading to a better insight in the caregiving role and thus in-patient care.